The content of Compounds and Bioactivity of the Eucalyptus sp species - Miftahul Jannah Abd Haris; Andi Nur Fitriani Abubakar; Syahdam Karneng; Iin Indriani; Herdie Idriawien Gusti; Surahmat; Triana Febrianti (Hayyan Journal, 2025)
Eucalyptus sp. is one of the plant genera from the Myrtaceae family which is widely known for its diverse secondary metabolite content and high biological activity. This study aims to systematically examine the diversity of active compounds and potential bioactivity of various Eucalyptus species, especially in the leaves, bark, seeds, and essential oils. Various compounds such as 1,8-cineole, citronellal, flavonoids, and phenolic compounds have been shown to contribute to pharmacological activities such as antioxidants, antimicrobials, anti-inflammatory, immunomodulators, anticancer, as well as natural insecticides and repellents. The results of the review indicate that these activities have great relevance in the development of biopharmaceutical products, cosmetics, and other health applications. The diversity of compounds and broad pharmacological effects place Eucalyptus as a very potential source of natural materials to be developed sustainably.